2018
DOI: 10.2147/dddt.s178698
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic effect of bone marrow mesenchymal stem cell-derived exosomes on steroid-induced osteonecrosis of the femoral head

Abstract: BackgroundAnimal studies have demonstrated the therapeutic effect of mesenchymal stem cells (MSCs) on osteogenesis, but little is known about the functions of exosomes (Exos) released by bone MSCs (BMSCs). Here, we investigated the effect of BMSC Exos on steroid-induced femoral head necrosis (SFHN) and explored the vital genes involved in this process.Materials and methodsBMSCs were isolated from healthy and SFHN rats. BMSC Exos were isolated using the Exosome Precipitation Kit and characterized by transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 43 publications
0
67
0
Order By: Relevance
“…In addition, Huang et al suggested that Icariin could improve the balance between osteogenic differentiation and adipogenic differentiation of BMSCs and then reduce the bone loss of SANFH rats [36]. These findings indicate that BMSCs are the key cytological basis for the pathogenetic mechanism of SANFH [6]. Therefore, exploring the molecules involved in the process of BMSC differentiation is expected to provide new ideas for the diagnosis and treatment of SANFH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Huang et al suggested that Icariin could improve the balance between osteogenic differentiation and adipogenic differentiation of BMSCs and then reduce the bone loss of SANFH rats [36]. These findings indicate that BMSCs are the key cytological basis for the pathogenetic mechanism of SANFH [6]. Therefore, exploring the molecules involved in the process of BMSC differentiation is expected to provide new ideas for the diagnosis and treatment of SANFH.…”
Section: Discussionmentioning
confidence: 99%
“…including adipocytes, chondrocytes, and osteoblasts [6]. Previous studies demonstrated that the change in osteogenic differentiation of BMSCs is related to SANFH [7,8].…”
mentioning
confidence: 97%
“…The fact that exosomes carry miRNAs which serve as important mediators of intercellular communication, has been proven to promote osteogenic differentiation of stem cells. 4,29,30 MiRNAs play a crucial role in bone development and homoeostasis. 8,31 Our findings revealed that overexpression of miR-130a-3p can promoted osteogenic differentiation but inhibited proliferation of ADSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous findings support the notion that the decreased osteogenic differentiation ability of BMSCs is closely related to the pathogenesis of ONFH. 14 A recent study reported that βEcd possesses multiple pharmacological actions, including protection against β-amyloid-induced apoptosis. 15,16 Previously, βEcd was shown to increase the differentiation of mesenchymal progenitor cells towards osteoblasts in vitro, which is consistent with the observation of an increased osteoblast surface following in vivo βEcd treatment.…”
Section: Discussionmentioning
confidence: 99%